IDENTIFIKASI SENYAWA AKTIF FRAKSI ETANOL DAUN SIRSAK (Annona muricata Linn.) SEBAGAI INHIBITOR α-AMYLASE - Eko Mugiyanto; Partomuan simanjuntak; Siswa Setyahadi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2017)
Diabetes mellitus (DM) is a chronic metabolic interference characterized by both postprandial and fasting glycemic increase with disturbances in carbohydrate, fat and protein metabolism. There has been much interest in the development of alternative medicine for type 2 diabetes. Annona muricata or sirsak has been use to cure cancer and according to American Association of Clinical Endocrinologist there was a significant increasing for patient cancer with obesity and diabetes. The goal of the present study was to provide in vitro evindence and chemical structure for potential inhibition of α-amylase. This was performed using ????-amylase from Aspergillus oryzae and the result was Ethanol fraction from Annona muricata leafes gave the highest inbitory activity against ????-amylase (IC50 73,54 ppm) furthermore inhibition of isolates compounds Fr.EtOH.4.2.3 gave IC50 0,12 ppm of ????-amylase. Analysis data and identification of active compounds is done by LC-MS and FT-IR, identification active compound of ????-amylase inhibitors is mixture of Muricatin C, cis-Reticulatacin-10-one and 3-Methylquercetin 7-[galactosyl-(1-4)-glucoside].Keywords: Diabetes, α amylase, annona muricata, sirsak